6-4 Elimination Using Multiplication SWABT: Solve a system of equations using elimination by multiplication. Important concepts: Understand exact opposites and eliminating a variable Understand solving an equation Understand a system of equations Step 1: Determine which variable to eliminate first Step 2: Multiply one or both equations to obtain exact opposites for the variable you wish to eliminate first. Step 3: Add the equations, eliminating one variable. Step 4: Solve the resulting equation for one variable. Step 5: Write one of the original equations. Step 6: Substitute the solution you found in step 4 into one of the original equations. Step 7: Solve for the other variable. Step 8: Write the solution as an ordered pair. Step 9: Check Example 1: 5x + 6y = -8 2x + 3y = -5 Step 1: I notice that 3y is a factor of 6y…making the “y” in this case 5x + 6y = -8 -2(2x + 3y = -5) easier to eliminate 5x + 6y = -8 Step 2:Multiply 2nd equation by -2 +( -4x -6y = 10) x =2 Step 3 & 4: Add & Solve for “x” 5x + 6y = -8 5(2) + 6y = -8 10 + 6y = -8 -10 -10 6y = -18 /6 /6 y = -3 (x, y) (2, -3) Step 5: Rewrite one of original equations Step 6: Substitute value found for x into original equation Step 7: Solve for “y” Check: Step 9 Step 8: write the solution as an ordered pair Example 2: 6x – 2y = 10 3x – 7y = -19 Step 1: I notice that 3x is a factor of 6x…making the “x” 6x - 2y = 10 -2(3x - 7y = -19) 6x - 2y = 10 6x – 2(4) = 10 6x - 8 = 10 +8 +8 6x = 18 /6 /6 x=3 (x, y) (3, 4) easier to eliminate in this case 6x - 2y = 10 Step 2:Multiply 2nd equation by -2 +( -6x +14y = 38) 12y = 48 Step 3: Add /12 /12 Step 4: Solve for “y” y=4 Step 5: Rewrite one of original equations Step 6: Substitute value found for “y” into original equation Step 7: Solve for “x” Step 8: write the solution as an ordered pair Now You Try: Example 3: 9r + q = 13 3r + 2q = -4 Step 1: I notice that q is a factor of 2q…making the “q” ___(9r + q = 13) 3r + 2q = -4 9r + q = 13 9(___) + q = 13 18 + q = 13 _____________ q = ___ (q, r) (___,___) easier to eliminate in this case -18r -2q = -26 Step 2:Multiply 1st equation by -2 +( ______________) -15r = -30 Step 3: _________ /-15 /-15 Step 4: Solve for “___” r = _____ Step 5: Rewrite one of original equations Step 6: Substitute value found for “___” into original equation Step 7: Solve for “____” Step 8: write the solution as an ordered pair Sometimes you must Multiply BOTH equations: Example 4: 4x + 2y = 8 3x + 3y = 9 -3(4x + 2y = 8) 4(3x + 3y = 9) 4x + 2y = 8 4x +2(2) = 8 4x + 4 = 8 -4 -4 4x = 4 /4 /4 x=1 (x,y) (1, 2) -12x - 6y = -24 12x + 12y = 36 6y = 12 Step 1: eliminate “x” Step 2: Mult 1st equation by -3, 2nd equation by 4 Step 3: Add equations Step 4: Solve for “y” /6 /6 y=2 Step 5: Rewrite one of original equations Step 6: Substitute y =2 Step 7: Solve for “x” Step 8: write the solution as an ordered pair Example 5: 6a + 2b = 2 4a + 3b = 8 -2(6a + 2b = 2) 3(4a + 3b = 8) 6a + 2b = 2 6a + 2(4) = 2 6a + 8 = 2 -8 -8 6a = -6 /6 /6 a = -1 (a,b) -12a -4b = -4 12a + 9b = 24 5b = 20 /5 /5 b=4 Step 1: eliminate “a” Step 2: Mult 1st equation by -2, 2nd equation by 3 Step 3: add equations Step 4 Solve for “b” Step 5: Rewrite one of original equations Step 6: Substitute b = 4 Step 7: Solve for “a” Step 8: Write the solution as an ordered pair Now You Try: Example 6: 2a + 5b = -10 5a – 3b= 6 __(2a + 5b = -10) __(5a -3b = 6) 2a + 5b = -10 2(___) + 5b = -10 ________________ _______________ /5 /5 b = ______ (a,b) (________,_______) ________________ Step 1: eliminate “____” ________________ Step 2: Mult 1st equation by___, 2nd ___________ equation by____ /31 /31 Step 3: add equations a = ____ Step 4 Solve for “___” Step 5: Rewrite one of original equations Step 6: Substitute a = 0 Step 7: Solve for “b”